Uma análise da contribuição do GeoGebra como recurso interativo para o estudo de áreas e volumes - Awila, Hakel Fernandes de (2017)
This paper was based on the objective of investigating and verifying how much the applets produced with the software GeoGebra can contribute to make the area and volume calculation, of the principal figures studied during the Basic Education, enlightening. In order to verify and investigate these contributions, freshmen from Mathematics graduation course of the Federal University of Santa Maria were invited to participate in weekly meetings aiming the study of the contents referred. In all, seven meetings were held, with an average duration of 2 hours each, in which it was executed a didactic sequence, following the Zabala’s principles (1998), that approached the area and volume contents combining the theories of significative learning and cognitive load. Before the study development, freshmen answered a questionnaire to verify their previous knowledges about these contents and a second questionnaire was answered at the end of the didactic sequence to, along with the research diary made during the planning execution, serve as data to the fulfillment of the objective. It was performed, therefore, a field research by means of an action research in the presence and participation of the researcher in the study environment (FLICK, 2004; FIORENTINI; LORENZATO, 2012). Analyzing the first questionnaire, it was possible to identify that freshmen worked these topics of Geometry in their basic formation by a mechanical learning, for they were answering the area and volume questions only with the application of formulas, incorrected, many times. Confronting the researcher’s diary and the second questionnaire with the first one, it was possible infer that, through the interaction developed with the applets in the didactic sequence, the students understood the justifications and/or certifications of the reasons why certain mathematical sentences express area and volume values.